a) √289225=√289√225=1715289225=289225=1715.
b) √21425=√2.25+1425=√6425=√64√25=8521425=2.25+1425=6425=6425=85.
c) √0,259=√0,25√9=0,53=530=160,259=0,259=0,53=530=16.
d) √8,11,6=√8116=√81√16=948,11,6=8116=8116=94.
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{x\sqrt{y}-y\sqrt{x}}{\sqrt{x}-\sqrt{y}}\)
\(=\frac{\left(x\sqrt{y}-y\sqrt{x}\right)\left(\sqrt{x}+\sqrt{y}\right)}{\left(\sqrt{x}-\sqrt{y}\right)\left(\sqrt{x}+\sqrt{y}\right)}\)
\(=\frac{\sqrt{xy}.x+xy-xy-\sqrt{xy}.y}{x-y}\)
\(=\frac{\sqrt{xy}.x-\sqrt{xy}.y}{x-y}\)
\(\frac{=\sqrt{xy}.\left(x-y\right)}{x-y}\)
\(=\sqrt{xy}\)
a, \(\sqrt{16x}=8\)ĐK : x >= 0
\(\Leftrightarrow4\sqrt{x}=8\Leftrightarrow\sqrt{x}=2\Leftrightarrow x=4\)
c, \(\sqrt{9\left(x-1\right)}=21\Leftrightarrow3\sqrt{x-1}=21\Leftrightarrow\sqrt{x-1}=7\)ĐK : x >= 1
\(\Leftrightarrow x-1=49\Leftrightarrow x=50\)
ĐKXĐ : x \(\ge2\)
Ta có \(\sqrt{x-2}-\sqrt{x+2}=2\sqrt{x^2-4}-2x+2\)
\(\Leftrightarrow\sqrt{x-2}-\sqrt{x+2}=2\sqrt{\left(x-2\right)\left(x+2\right)}-\left(x-2\right)-\left(x+2\right)+2\)
<=> \(\sqrt{x-2}-\sqrt{x+2}=-\left(\sqrt{x-2}-\sqrt{x+2}\right)^2+2\)
Đặt \(\sqrt{x-2}-\sqrt{x+2}=y\)
=> y = -y2 + 2
<=> y2 - y - 2 = 0
<=> (y + 1)(y - 2) = 0
<=> \(\orbr{\begin{cases}y=-1\\y=2\end{cases}}\)
Khi y = -1
<=> \(\sqrt{x-2}-\sqrt{x+2}=-1\)
=> \(\left(\sqrt{x-2}-\sqrt{x+2}\right)^2=1\)
<=> \(\left(x-2\right)+\left(x+2\right)-2\sqrt{\left(x-2\right)\left(x+2\right)}=1\)
<=> \(2x-1=2\sqrt{\left(x-2\right)\left(x+2\right)}\)
=> 4x2 - 4x + 1 = 2(x - 2)(x + 2)
<=> 4x2 - 4x + 1 = 2x2 - 8
<=> 2x2 - 4x + 9 = 0 (vô lý) => TH1 loại
Khi y = 2 =>\(\sqrt{x-2}-\sqrt{x+2}=2\)
=> \(\left(\sqrt{x-2}-\sqrt{x+2}\right)^2=4\)
<=> \(2x-2\sqrt{\left(x-2\right)\left(x+2\right)}=4\)
<=> \(2x-4=2\sqrt{\left(x-2\right)\left(x+2\right)}\)
=> (2x - 4)2 = 4(x - 2)(x + 2)
<=> 4(x - 2)2 = 4(x - 2)(x + 2)
<=> -16(x - 2) = 0
<=> x = 2 (tm)
Vậy x = 2
????????
Weo
-tt-